Internet caravan - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In mid-March, 2002, the Mauritanian government gave a bustling send-off to its new Internet caravan to introduce the Internet to rural communities. It is travelling through the Hodh El Chargi region, near the border with Mali and is set to...